Pengaruh Jintan Hitam Terhadap Kelancaran Produksi Asi Pada Ibu Menyusui - Sri Yanti; Sri Winarni (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2023)
Efforts to increase breast milk production can be done by carrying out early and routine breast care, improving breastfeeding techniques, or by consuming foods that can affect breast milk production. Indonesia is a country that is rich in various types of plants which are useful as medicinal plants. Some of them are efficacious as lactagogums such as katuk plants, lampes, sweet fennel, thorn spinach, bidara upas, blustru, chicken dadap, bitter black cumin, moringa, jackfruit, patikan kebo, pulai, curcuma, turi, and young papaya. Black cumin is one of them. spices containing lactagogum. This spice is in the form of black seed grains which have been known for thousands of years and are widely used by the people of India, Pakistan and the Middle East to treat various diseases. This type of plant has been referred to as a medicinal plant in the early development of Islam (Trubus, 2012). Lactagogum is a drug that can increase or facilitate milk production. Synthetic lactagogum is little known and relatively expensive. This causes the need to look for alternative lactagogum drugs.